Investigating Problem Issues in Customer Service Using Combined Transport - Aldona Jarašūnienė; Martynas Razgus (The Baltic Journal of Road and Bridge Engineering)
With the growth in the number of shipments and the increasing costs of transport and air pollution caused by transport activities around the world, the past decade has seen a search for alternative freight transport methods to reduce these factors. Scientific background and assumptions: it is argued that in combined transport, the transit time is the same as in single mode transport; customers’ needs have increased. The research object of the article: the operation of combined transport and its impact on the quality of customer service. The analytical and scientific part analyses the concept of logistics, its operational processes, as well as presents the main components of the activity in theoretical and scientific aspects, which are used to carry out other analyses of the scientific literature on customer service, combined transport activity, which are necessary for the research. The research part, which is based on the collected statistical data, best practices in foreign countries and an expert survey, seeks to identify the real issues of combined transport and the areas that affect customer service. The results section presents the developed model regarding the solution that can be applied to eliminate or reduce and improve customer service performance in a combined transport mode.